Activities of soviet special services for the liquidation of the Greek Catholic Church in the Transcarpathian Ukraine - Vedeneev Dmytro (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article draws on little-known documents of Soviet special services and sheds light on law enforcement activities of the Ministry of State Security of the USSR and Ukrainian SSR in the process of liquidation of the Greek Catholic Church in the Transcarpathian Ukraine in 1949. The events in Transcarpathia, where the “self-dissolving” of the Uniate Church took place in 1948‒1949, did not receive a full and detailed description before. Scholars did not pay much attention to the activities of special services that in many respects made possible the reuniting of Greek Catholics and the Orthodox Church. The study of these events has become possible only recently as previously classifi ed documents have been made public. This article examines the confessional situation and social and religious attitudes in the region after its inclusion in the USSR in 1945, resistance of the clergy and hierarchs against incorporating the Greek Catholic Church into the Orthodox Church. The article also studies the mechanism of law enforcement and special propagandist activities of the special service in destroying the local community of Greek Catholics, in creating points of infl uence among the clergy of the Greek-Catholic Church, in preparation of the act of eliminating the Church Union in the Transcarpathian Ukraine according to the “Plan of Law Enforcement Activities for the Liquidation of the Greek-Catholic Church in the Transcarpathian Region of the Ukrainian SSR” approved by Minister of State Security of the Ukrainian SSR S.R. Savchenko on 14 January, 1948. Using previously unknown documents, this article sheds light on the circumstances of the death of the leader of the Greek Catholic Church of Transcarpathia bishop Theodor Romga (Russ. Теодор Ромжа), who might have become victim of a terrorist act of state security organs because of his relentless resistance against the elimination of the Church Union in the region. Besides, the documents identifi ed allow one to doubt certain “sensational versions” of the hierarch’s death, among others described by P.A. Sudoplatov. The article discusses features of liquidation of the Union, consequences of Mukachevo act of 1949 and the subsequent measures of state security organs of the Ukrainian SSR.